66=6(g+2)

Simple and best practice solution for 66=6(g+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 66=6(g+2) equation:


Simplifying
66 = 6(g + 2)

Reorder the terms:
66 = 6(2 + g)
66 = (2 * 6 + g * 6)
66 = (12 + 6g)

Solving
66 = 12 + 6g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-6g' to each side of the equation.
66 + -6g = 12 + 6g + -6g

Combine like terms: 6g + -6g = 0
66 + -6g = 12 + 0
66 + -6g = 12

Add '-66' to each side of the equation.
66 + -66 + -6g = 12 + -66

Combine like terms: 66 + -66 = 0
0 + -6g = 12 + -66
-6g = 12 + -66

Combine like terms: 12 + -66 = -54
-6g = -54

Divide each side by '-6'.
g = 9

Simplifying
g = 9

See similar equations:

| -4-5x+2=-21x+7-5x | | 7x-53x+12= | | 3j+10=67 | | xtan(0.5x)=2 | | 2(x)+22=4(x+3) | | 3w^3-18w^2+15w=0 | | 4/(4x^2-x-24)=7/(7c^2-7c-36) | | 3(3x-6)=6(4x-8)-5x | | 1/2y−8=−10 | | 2x-5+2(3x)+13=-2-2x+(16-5) | | (9b-6)-4(2b+2)=-7 | | 100=34 | | 5-4x=11x | | 5-(6-3n)=2 | | G(x)=x^2+3x-54 | | 12x/4=-2y/2 | | G(x)=x^2+9x+20 | | 2=x/-5 | | 9b-9b=11(b-7)+8(b+12) | | 2y^2+18y+80=0 | | -4/7en-3/7en= | | -8=1x+-12-10 | | (3x-4)(7x+4)=0 | | x^2=36-5x | | 4x-5+2(3x)+17=-2-3x+(9-5) | | 13-x=-1 | | -4/7en--3/7en= | | Y=27x+10.50 | | 4(3y-1)=-40 | | 7x-2(x-4)= | | 10x+5+8=12x-3x+80 | | V+5v=42 |

Equations solver categories